A review of state of health and remaining useful life estimation methods for lithium-ion battery in electric vehicles: Challenges and recommendations - Lipu M.S.H.; Hannan M.A.; Hussain A.; Hoque M.M.; Ker P.J.; Saad M.H.M.; Ayob A. (Elsevier Ltd, 2023)
Aging of materials; Battery management systems; Electric automobiles; Electric vehicles; Environmental impact; Fossil fuels; Health; Ions; Proven reserves; Electric Vehicles (EVs); Estimation approaches; Internal and external factors; Issues and challenges; Remaining useful lives; State of health; Technological development; Thermal runway; Lithium-ion batteries